Levantamento de Meloidogyne incognita em lavouras de algodão no noroeste do Paraná e seleção de genótipos de algodoeiro com resistência a Meloidogyne incognita raça 3 - Pires, Ely (2007)
Among the pathogens that reduce the cotton productivity in Brazil, Meloidogyne incognita is one of the most important by causing yield losses and for being widespread. The most recommended control methods to this species are the use of resistant cultivars and crop rotation systems. In Paraná, M. incognita races 3 and 4 have already been reported as cotton parasites. The present work aimed at knowing the distribution of M. incognita on cotton at the northwest of Paraná State, as well as to find out about the prevalent race in this region. This work also aimed at selecting sources of resistance to M. incognita race 3 in cotton genotypes. A survey was carried out in order to know the distribution of M. incognita in cotton areas at the northwest of Paraná State. Cotton plants showing galls on the root system were sampled in infested areas from the cities of Altônia, Iporã, Moreira Sales, Mariluz, Pérola and Umuarama. Single egg masses were settled and reproduced on tomato plants cultivar Rutgers and left in a greenhouse at 25oC. The race identification was carried out based on the infection developed on differential hosts, inoculated with 5.000 j2 and cultivated in pots at 25oC. The evaluation of the race tests occurred 60 days after the inoculation. To assess the resistance of cotton genotypes to M. incognita, essays were developed from both greenhouse condition and field and contained 31 treatments and 10 replications. The greenhouse essays followed a completely randomized design while the field experiment was taken in randomized blocks. Regarding the greenhouse tests, it was inoculated 5.000 J2/cotton genotype containing two leaves. The evaluation was taken at 70 and 120 days after inoculation and focused on the parameters number of galls and reproduction factor (RF). The field experiment was assessed taking into account the gall index scored by notes. The results showed that M. incognita race 3 was detected from cotton plants in all the cities. The parameter Reproduction Factor (RF) was the most suitable to the selection of cotton genotypes in greenhouse at 120 days after inoculation. The assessment, taken from scoring notes in the field experiment, mixed genotypes with different levels of resistance and should be carried out only to confirm the resistance of cotton genotypes previously evaluated in greenhouse by the RF. The three monospecific isolates were important to the screening of resistant cotton genotypes to M. incognita race 3. The genotypes CD 05-419, CD 05-1222, CD 05-1087, CD 05-1323 e CD 05-1170 were resistant against M. incognita race 3, in greenhouse conditions and also in the field experiment. The screened genotypes will be tested against other specific cotton pathogens and also against multiple cotton diseases